Effect of protected fat, yeast, niacin, zinc and chromium supplementation on the productive performance of heat-stressed Karan Fries heifers - Purwar, Vaibhav (Indian Journal of Dairy Science, 2018)
The main aim of this study was to evaluate the effectof feed supplements and additives on the productive performanceof growing heifers during summer season. A total of 18 KaranFries (KF) heifers were randomly selected and divided into twogroups, i.e. control and treatment. The basal ration for both controland treatment groups was the same. However, the treatment groupwas supplemented with protected fat, yeast, niacin, zinc, andchromium. Various body growth-related parameters and plasmaInsulin-like growth factor 1 (IGF-1) were estimated fortnightly upto 120 days post-feeding. The body weight, DMI/100kg BW andgain in height were numerically higher in the treatment group ascompared to control group but it didn’t show any significantdifference. Average daily gain (ADG) and heart girth gain (HGG)were significantly (P